2017
DOI: 10.13189/ujer.2017.050801
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Healthy Lifestyle Behaviors of High School Students

Abstract: Healthy lifestyle behaviors can be defined as all the behaviors believed and applied by individuals to be healthy, maintain health and be protected from diseases. This study aims to determine the healthy lifestyle behaviors of high school students studying at the high schools in the Province of Elazig, Turkey. The study population of this descriptive study consists of students studying at the high schools located in the Cumhuriyet neighborhood located in the city center of the Province of Elazig. Simple random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 2 publications
1
6
0
4
Order By: Relevance
“…The literature review found plentiful theoretical studies that highlight the approaches to developing the healthy lifestyle behaviours in the students (Bakouei et al, 2019;Caliskan et al, 2018;Celebi et al, 2017;Kabakci, 2019). Pedagogical literature mostly focuses on pedagogical strategies targeting the physical activity or social skills of the students and schoolchildren aimed at establishing the environment that favours their successful learning and life enjoyment (Dudley, 2011;Lander et al, 2019;Ningthoujam et al, 2017;Syarifuddin et al, 2020;Zhang, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature review found plentiful theoretical studies that highlight the approaches to developing the healthy lifestyle behaviours in the students (Bakouei et al, 2019;Caliskan et al, 2018;Celebi et al, 2017;Kabakci, 2019). Pedagogical literature mostly focuses on pedagogical strategies targeting the physical activity or social skills of the students and schoolchildren aimed at establishing the environment that favours their successful learning and life enjoyment (Dudley, 2011;Lander et al, 2019;Ningthoujam et al, 2017;Syarifuddin et al, 2020;Zhang, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It adds further that 60% of the quality of an individual’s life correlates on an individual’s behavior and lifestyle [ 10 ] and even suggested recommendations that Healthy Lifestyle can reduce the risk of avoidable health problems and improve a person’s quality of life. Research publications supported the notion of the WHO have shown that healthy lifestyle practices reduce disease incidence and mortality rates [ 11 - 13 ]. People who practiced healthy lifestyle behaviors can resist health risks associated to disability and disease in later life.…”
Section: Introductionmentioning
confidence: 99%
“…Sağlık davranışı kişinin hastalıkları önleyebilmek için gerçekleştirdiği herhangi bir aktivite, benimsenen bir davranış veya bir eylemdir 1 . Sağlıklı yaşam biçimi davranışları hastalıklardan korunma, sağlığın sürdürülmesi ve sağlıklı olmak için kişinin uyum gösterdiği ve inandığı tüm davranışlar olarak tanımlanabilir.…”
Section: Introductionunclassified
“…Sağlıklı yaşam davranışlarına gerektiği önemi vermeyenlerde çeşitli sağlık sorunları ortaya çıkabilir. 1 Bu kapsamda olumlu sağlıklı yaşam davranışları içerisinde tütün ve alkol kullanmama, yeterli ve dengeli beslenme, düzenli egzersiz, sağlık sorumluluğu, hijyenik önlemler ve stres yönetimi yer alır. 1,3 Küresel hastalık yükü (2013) araştırmasında kişinin davranışsal özelliklerinin de küresel ölüm nedenleri arasında yer aldığı görülmektedir.…”
Section: Introductionunclassified
See 1 more Smart Citation